Professor Jerzy Neyman – Some Reflections - Kordos, Jan (Lithuanian Journal of Statistics, 2011)
The author cooperated with Professor Jerzy Neyman in Poland in 1958 on the subject of sampling surveys.He begins with Neyman’s ancestors to explain his connections with Poland, and Neyman’s primary, secondary and universityeducation. Next the author focuses on Neyman’s period in Poland in the years 1921-1934, paying special attention to Neyman’sinvolvements in the development of theory and practice of sampling surveys.He begin with major developments in sampling at the 1925 and 1927 sessions of the International Statistical Institute.This is the background for discussion of Neyman’s contribution to theory and practice of sampling. Next Neyman’s initialcontribution to the theory of sampling in the 1920s and his cooperation with Karl Pearson is emphasized. Before presentingNeyman’s famous 1934 paper, which synthesizes his own contributions and those of others, and effectively demolishes theidea of purposive sampling, the author stresses that main ideas of this paper are presented in Neyman’s booklet prepared in1932 in Polish and published in 1933. Summary of this booklet is given in Annex 1.Finally, special attention is paid to the co-operation of Professor Neyman, after the Second World War, with Polish samplingstatisticians, and mainly with the Central Statistical Office of Poland. At the end, some reflections of the author are presented.